Integrating net rainfall calculation in deep learning-based surrogate modeling frameworks for 2D flood prediction - Juan F. Farfán-Durán; Carlos Montalvo; Luis Cea; João P. Leitão (Journal of Hydrology, 2025)

A Robust Method to Update Local River Inundation Maps Using Global Climate Model Output and Weather Typing Based Statistical Downscaling - M. Bermúdez; L. Cea; E. Van Uytven; P. Willems; J.F. Farfán; J. Puertas (Water Resources Management, 2020)

Adipocyte proteome and secretome influence inflammatory and hormone pathways in glioma - J. Almeida; J. Costa; P. Coelho; V. Cea; M. Galesio; J. P. Noronha; M. S. Diniz; C. Prudêncio; R. Soares; C. Sala; Rúben Fernandes (Metabolic Brain Disease, 2019)

Abies pinsapo Boiss. Transcriptome Sequencing and Molecular Marker Detection: A Novel Genetic Resources for a Relict Mediterranean Fir - A Pérez-González; M Marconi; I Cobo-Simón; B Méndez-Cea; P Perdiguero; R Linacero; J C Linares; F J Gallego (Forest Science, 2018)

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

Facilitation of the non-native annual plant Mesembryanthemum crystallinum (Aizoaceae) by the endemic cactus Eulychnia acida (Cactaceae) in the Atacama Desert - Jaime Madrigal-González; Alex P. Cea; Leticia A. Sánchez-Fernández; Karina P. Martínez-Tillería; Juan E. Calderón; Julio R. Gutiérrez (Biological Invasions, 2013)

Parallel activation of Ca2+-induced survival and death pathways in cardiomyocytes by sorbitol-induced hyperosmotic stress - M. Chiong; V. Parra; V. Eisner; C. Ibarra; C. Maldonado; A. Criollo; R. Bravo; C. Quiroga; A. Contreras; J. M. Vicencio; P. Cea; J. L. Bucarey; et al. (Apoptosis, 2010)